Changes in mortality rates among extremely preterm infants born before 25 weeks' gestation: Comparison between the 2005 and 2010 nationwide surveys in Japan. (April 2021) - Itabashi, Kazuo; Miyazawa, Tokuo; Kusuda, Satoshi; Wada, Kazuko
Abstract: Background: There is no consensus as to whether the outcomes of extremely preterm infants born <25 weeks' gestation have been constantly improving. Aims: Our study aimed to clarify changes in mortality during hospitalization among extremely preterm infants. Study design: Comparison of mortality rates between the 2005 and 2010 retrospective nationwide surveys in Japan. Subjects: Extremely preterm infants born <25 weeks' gestation in Japan and registered in the nationwide surveys, 802 infants in 2005 and 797 in 2010, respectively. Outcomes: Mortality rates stratified by gestational age. Results and conclusion: Mortality rates <25 weeks' gestation decreased from 36.4% to 25.6% (difference − 10.8% [95% confidence interval CI: −15.3%, −6.2%]) in 2010 compared to 2005. Gestational age-specific mortality rates were lower in 2010 compared to 2005, except for 24 weeks' gestation: 66.0% vs. 50.0% (difference: −16% [95% CI: −29.8%, −21.2%]) and 45.7% vs. 25.5% (difference: −20.2%, [95% CI: −28.1, −12.3%]) at 22, and 23 weeks' gestation, respectively. After adjusting for explanatory variables, the probability of death during hospitalization in 2010 was significantly lower in infants born <25 weeks' gestation (adjusted odds ratio [aOR] 0.597 [95% CI: 0.471, 0.757], but when stratified by gestational age, it was only significant for infants born at 23 weeks' gestation (aOR 0.439 [95% CI: 0.303, 0.636]). In conclusion, the mortality rates among infants born <25 weeks' gestation have been steadily improving from 2005 to 2010 in Japan, but the practice for infants born at 22 weeks' gestation is still challenging. Highlights: Mortality rates have decreased for preterm infants born before 25 week's gestation. Mortality among preterm infants born at 23 weeks' gestation significantly decreased. Management of infants born at 22 weeks' gestation is still difficult in Japan.